HOTVOLC: the official French satellite-based service for operational monitoring and early warning of volcanic ash plumes - Guéhenneux, Yannick; Gouhier, Mathieu (Bulletin of Volcanology, 2024)
International audience Early detection of volcanic ash clouds is crucial to aviation safety and airspace surveillance. With the increase in air traffic and the frequency of volcanic eruptions, the need for effective warning procedures and improved detection methods has become obvious. The eruption of the Eyjafjallajökull volcano in 2010 showed that air traffic operations were severely disrupted and highlighted the importance of effective communication strategies between stakeholders. To improve monitoring capabilities, satellite techniques have become essential due to their wide coverage and rapid response. This article presents the HOTVOLC 3.0 web-Geographic Information System (GIS) interface, an enhanced version of the French operational monitoring platform developed at the Observatoire de Physique du Globe de Clermont-Ferrand (OPGC) and certified by the Institut National des Sciences de l'Univers of the Centre National de la Recherche Scientifique (CNRS-INSU). By integrating data from the Meteosat Second Generation (MSG) satelli